A double button adjustable loop device is biomechanically equivalent to tension band wire in the fixation of transverse patellar fractures—A cadaveric study. Issue 2 (February 2017) - Han, Fucai; Pearce, Christopher Jon; Ng, David Q.K.; Ramruttun, Amit K.; Chong, Desmond Y.R.; Murphy, Diarmuid; Lim, Chin Tat; Lee, Bernard C.S.
Abstract: Introduction: Tension-band wire fixation of patellar fractures is associated with significant hardware-related complications and infection. Braided polyester suture fixation is an alternative option. However, these suture fixations have higher failure rates due to the difficulty in achieving rigid suture knot fixation. The Arthrex syndesmotic TightRope, which is a double-button adjustable loop fixation device utilizing a 4-point locking system using FibreWire, may not only offer stiff rigid fixation using a knotless system, but may also obviate the need for implant removal due to hardware related problems. The aim of our study is to compare the fixation rigidity of patella fractures using Tightrope versus conventional tension-band wiring (TBW) in a cadaveric model. Materials and methods: TBW fixation was compared to TightRope fixation of transverse patella fractures in 5 matched pairs of cadaveric knees. The knees were cyclically brought through 0–90° of motion for a total of 500 cycles. Fracture gapping was measured before the start of the cycling, and at 50, 100, 200 and 500 cycles using an extensometer. The mean maximum fracture gapping was derived. Failure of the construct was defined as a displacement of more than 3 mm, patella fracture or implant breakage. Results: All but one knee from each group survived 500 cycles. The two failures were due to a fracture gap of more than 3 mm during cycling. There was no significant difference in the mean number of cycles tolerated. There was no implant breakage. There was no statistical significant difference in mean maximum fracture gap between the TBW and TightRope group at all cyclical milestones after 500 cycles (0.3026 ± 0.4091 mm vs 0.3558 ± 0.7173 mm, p = 0.388). Conclusions: We found no difference between the TBW and Tightrope fixation in terms of fracture gapping and failure. With possible lower risk of complications such as implant migration and soft tissue irritation, we believe tightrope fixation is a feasible alternative in fracture management of transverse patella fractures.